Health and well-being in small island communities: a cross-sectional study in the Solomon Islands - Furusawa, Takuro; Pitakaka, Freda; Gabriel, Spencer; Sai, Akira; Tsukahara, Takahiro; Ishida, Takafumi (BMJ open, 2021)
ObjectivesThis study explored the health problems of inhabitants of small South Pacific Islands under the influence of climate change, focusing on three communities in the Solomon Islands.DesignCross-sectional study of the Solomon Islands’ populations.SettingA field survey was conducted in Taro Island, a small, urbanised island with a whole-community relocation plan; Manuopo community of Reef Islands, a small remote island on an atoll environment and Sasamungga, an intermediately urbanised community on a larger island. The Sasamungga community was used for comparison.ParticipantsEach community’s participants were recruited through local health authorities, and 113, 155 and 116 adults (aged 18+ years) from Taro, Manuopo and Sasamungga, respectively, participated voluntarily.MethodsEach participant’s body height, weight and body mass index were measured. A drop of blood was sampled for malaria testing; glycated haemoglobin and C reactive protein levels, measured from another drop of blood, were markers for diabetes and inflammation, respectively. The Primary Care Screening Questionnaire for Depression measured depressive mental states.Primary and secondary outcome measuresRegarding health status, the dependent variables—communicable diseases, non-communicable diseases and mental state—and independent variables—differences in communities and socioeconomic status—were measured through health check-ups and interviews of individual participants.ResultsTaro Island inhabitants had a higher risk of obesity (OR 1.13, 95% CI 1.02 to 1.27, p=0.0189), and Manuopo inhabitants had a higher risk of depression (1.25, 95% CI 1.08 to 1.44, p=0.0026) than Sasamungga inhabitants. Manuopo inhabitants recognised more serious problems of food security, livelihood, place to live and other aspects of daily living than other communities’ inhabitants.ConclusionsThe three small island communities’ observation identified different health problems: the urbanised community and remote community had a high risk of non-communicable diseases and mental disorders, respectively. These health problems should be monitored continuously during future climate-related changes.